2021
DOI: 10.1017/jfm.2021.215
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds number effect on the response of a rough wall turbulent boundary layer to local wall suction

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The above observations suggest that the rough-wall TBL under PGs responds first to the roughness and then to the PGs; the closer to the wall, the more dominant is the roughness effect. This is consistent with the finding of Ghanadi & Djenidi (2021a), who showed that roughness prevents relaminarization downstream of a local wall suction (or equivalently strong local FPG). It is also worth noticing that the boundary layers in the present study are not fully developed and hence the values may change in scenarios where fully developed state is achieved.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The above observations suggest that the rough-wall TBL under PGs responds first to the roughness and then to the PGs; the closer to the wall, the more dominant is the roughness effect. This is consistent with the finding of Ghanadi & Djenidi (2021a), who showed that roughness prevents relaminarization downstream of a local wall suction (or equivalently strong local FPG). It is also worth noticing that the boundary layers in the present study are not fully developed and hence the values may change in scenarios where fully developed state is achieved.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the value of the ratio u /U is approximately 0.3 at a distance y = k and decreases continuously as y increases, as shown in figure 13 reporting the distribution of u /U. Accordingly, we focus the spectral analysis on the region delimited y = k (the vertical line in figure 12) where the Taylor hypothesis is appropriate (further discussions on the Taylor hypothesis for the present rough-wall TBL can be found in Ghanadi & Djenidi (2021a)). Note that for clarity, the spectral analysis is carried out for location IV only; similar results are obtained for the other locations.…”
Section: Roughness Elementmentioning
confidence: 77%
“…They found that the localized blowing results in an increase in the time-averaged streamwise velocity but a reduction in the maximum streamwise-averaged Reynolds shear stress and turbulent kinetic energy. Furthermore, Djenidi et al [45,46] experimentally investigated the wall suction effects on the rough-wall turbulent boundary layer. It was seen from the velocity spectra contour maps that the suction decreases the energy at all scales of motion across the boundary layer.…”
Section: Introductionmentioning
confidence: 99%